Development of chrysin loaded poloxamer micelles and toxicity evaluation in fish embryos - Sassa-deepaeng T. (2017)
Poloxamer micelles promise safety and efficacy for many water insoluble drugs. Chrysin has been reported to have anticancer, anti-inflammatory, antioxidant, and anti-aromatase activities but its water insoluble properties limit its pharmaceutical application. In the present study, chrysin loaded poloxamer micelles were developed. Two types of poloxamers, Pluronic F-68 and Pluronic F-127 were compared. It was found that chrysin loaded Pluronic F-68 micelles (CS-P68) and chrysin loaded Pluronic F-127 micelles (CS-P127) obviously increase the aqueous solubility of chrysin. The results also indicated that the type of polymer and ratio of drug to polymer affected size and desirable characteristics of the micelles. The micelle system of CS-P68 and CS-P127 formed at drug to polymer ratios of 1:4 and 1:2, respectively, was found to be the most suitable monodispersed system with a nanosize-range diameter. The in vivo study in zebrafish eggs indicates that the toxicity of CS-P68 and CS-P127 is a dose response. CS-P68 and CS-P127 at a drug dose of 10 ng/mL or less is safe for zebrafish embryo growth. The results of this study indicate enhanced water solubility of chrysin. Chrysin loaded poloxamer micelles are promising for further use in in vivo studies in mammalian animals and humans. © 2016, International Research and Cooperation Association for Bio & Socio-Sciences Advancement. All rights reserved.